Lonely Planet's guide to death, grief and rebirth : how global grieving customs can help us live (and die) well - Isalska, Anita; Bindloss, Joseph (Lonely Planet Global Limited, 2024)
"How do cultures around the world grieve their loved ones? From Tibetan sky burials and Māori mourning customs to Swedish death cleaning, Irish wakes and Buddhism's bardos, this enthralling book reveals the different ways in which people approach life's one certainty: death. Through the four themes of celebrating, commemorating, mourning and offering, we illuminate more than 35 life-affirming traditions. Along the way, we'll highlight places and festivals that can be visited, such as Mexico's Day of the Dead and the catacombs of Paris. Local contributors provide personal perspective on many customs, revealing how they can help us all live (and die) well."--Page [4] of cover.